Investigating into the need of Total productive maintenance (TPM) at AL-Arz - Abo AL-Soud, Hazem; AL-Jabi, Hiba; Sharif, Lana; Draghmeh, Lara; Shehadeh, Sabreen (My University, 2017)
TPM is a generic maintenance philosophy that transforms maintenance activities from what is considered to be into an essential part of the business. In TPM, maintenance and downtime is integrated within the production system and scheduled as an essential part of the manufacturing process. This project introduces TPM main concepts and presents case studies to highlight the importance of TPM from human factor and technology perspectives.